Randomized Observational Studies on the Economics of Therapies – Biometrical Experience of Two Trials - Högel, J.; Rodloff, A. C.; Büchele, G.; Gaus, W. (Methods of Information in Medicine, 1998)
Economic studies in medicine are intended to investigate costs, associated with a particular problem dealing with the indication, diagnosis or therapy, for instance, whether the high costs involved in a highly intensive or innovative therapy could be balanced by the eventual savings made, due to the shorter periods of treatment. In such situations a randomized controlled trial is necessary to find out which therapy or which therapeutical strategy is least expensive in the long run. Economic studies do, however, present some specific problems. Making a list of all the cost-relevant treatment items can be very laborious, but the use of flat rates and lump sums alone cannot lead to a complete cost analysis. Often, costs between hospitals vary more than between treatment regimens.Early and sudden deaths incur low costs and may bias the results. Furthermore, costs are distributed with a long and heavy upper tail incltJding extreme outliers. This does, in fact, complicate the estimation of the sample size. In this article, these problems are outlined and, with the help ofthe data obtained from two randomized economic trials in health care, solutions are proposed and discussed.
Keywords: Pharmaco-Economy; Economic Studies; Costs Analyses; Nosocomial Pneumonia; Peritonitis; Randomized Studies